Relation between Religious Understanding and Women's Life - Desi Erawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study examines how religious understanding and women's life are in Kahayan riverside, Central Kalimantan, Indonesia. This study aims to see whether there is a relationship between the religious understanding and women’s social life. The research method used is naturalistic qualitative by taking purposive samples; there are 12 participants consisting of 5 male laborers or  private company workers and 5 housewives, added by supporting informants namely Rukun Warga (RW) and one leader of an equally-sub district area namely RT as participants who understand the pattern of life in the community. Data were obtained through observations for two months in May - June 2019. The data analysis was done by collecting daily records every week and then they were evaluated based on needs. This study found out that a religious doctrine that is textually normative is very influential on the mindset among women/mothers so that it is shaped in their social life.